AKTIVITAS ANTIOKSIDAN DAN ANTIJAMUR SENYAWA ATSIRI BUNGA CEMPAKA PUTIH (Michelia alba) - I Gusti Agung Gede Bawa (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2011)
Isolation of white tropical magnolia’s (Michelia alba) essential oil by maseration method was carried out. Antifungal activity test was conducted by measuring resistibility against Candida albicans growth, whereas antioxidant activity test was conducted with spectroscopy technique by using Difenilpikril hidrazin (DPPH) as antifree radical. Compound contents analysis of the isolate was carried out by Gas Chromatography-Mass spectroscopy (GC-MS).From 1000 grams of white tropical magnolia’s flower 3.18 grams n-hexane extract, 1.19 grams of chloroform extract, and 0.88 grams of ethyl acetate extract were gained. The retardation area for the three extracts were 0 mm. Free radical damping percentage were 24.47% for the first 5 minutes and 79.14% after 60 minutes for n-hexane extract, 21.72% for the first five minutes and 25% after 60 minutes for chloroform extract, 21.93% for the first five minutes and 39.87% after 60 minutes for ethyl acetate extract. Compound analysis was carried out for n-hexane extract that have the highest antioxidant activity. GC-MS analysis showed that white tropical magnolia’s flower had 6 major component i.e. 1,3-Benzioxole,5-(2-propenyl), cyclohexane; 1-ethenyl-1-methyl-2,4-bis (1-methylethenyl); Butanoic acid; 3-methyl-,2-phenylethyl ester; 9,12-Octadecadienoic acid, methyl ester; Tricosane; Pentacosane.